Pattern of admission and outcome of patients in Trauma Intensive Care Unit, Emergency Department, Hospital Universiti Sains Malaysia - Ky, Wong Choc (2020)
Major trauma is one of the main causes of hospitalization and consumes a significant amount of health care budget. The role of Trauma ICU (TICU) is vital in the chain of trauma care to ensure rehabilitation and sustainable critical care for a better survival outcome. This study is conducted to find out demographic patterns and predictors that can affect the outcomes of trauma patients. This retrospective, observational study was conducted in TICU, Hospital UniversitiSains Malaysia (HUSM) between January 1, 2016 and December 31, 2018. A total of 108 trauma patients were included in this study. Males were 6 times more likely than the females to sustain trauma. All cases were exclusively blunt trauma (99.1%) and mainly attributed to road traffic accidents (92.6%). Approximately seventy six percent were intubated and 7.8% died in ICU. In terms of trauma clinical scoring, 25% (p= 0.001) with GCS score < 4, 46.9% (p= 0.000) with RTS score < 5.5 and 15.6% (p= 0.012) with APACHE II score > 28 demonstrated prolonged ICU stay (> 7 days). Meanwhile 62.5% (p= 0.000) with GCS < 4, 75% (p= 0.000) with RTS < 5.5 and 75% (p= 0.000) with APACHE II > 28 died in TICU. Trauma patients who had prolonged ICU stay demonstrated 4 times higher odds to be ventilated (adj B= 4.012; p= 0.021). Besides that, those who had prolonged ICU stay were 8.5 times higher odds to get sepsis (adj OR= 8.532; 95% CI: 2.710, 26.863; p= 0.000) and 7 times higher odds to get AKI (adj OR= 7.131; 95% CI: 1.464, 34.733; p= 0.015). Blood transfusion led to 5 folds higher odds in rhabdomyolysis in trauma (adj OR= 4.968; 95% CI: 1.821, 13.549; p= 0.002). Clinical scoring in trauma has stronger association to predict mortality than length of ICU stay. Ventilation period and trauma related complications are closely related with length of ICU stay.